Balloon Atrial Septostomy in a Premature Infant - Connie Choi, MD; Troy Johnston, MD; Agustin Rubio, MD; Brian Morray, MD (JACC: Case Reports, 2023)
Balloon atrial septostomy (BAS) in premature and very low weight infants has not been described. We present a successful BAS in a 1.4-kg, 13-day-old ex–31 6/7–week infant with dextro-transposition of the great arteries and a restrictive atrial septum. (Level of Difficulty: Advanced.)